Comparison of Common Risk Factors and Comorbidities among Patients with and without Hypertension in Bangladesh - Wahiduzzaman, Miah; Kabir, AKM Shamsul; Siddiki, Adib; Khokon, Kamruzzaman; Hossain, Solaiman; Chowdhury, Mohiuddin Humayun Kabir; Haque, Mosharul; Ahsan, Mohammad Morshedul; Ghosh, Paritosh Kumar; Yasmin, Abida (Cardiology and Cardiovascular Medicine, 2024)
Background: Hypertension is a significant public health issue globally and particularly in low-middle-income countries like Bangladesh. This study aims to observe the prevalence of hypertension in Bangladesh and compare the risk factors and comorbidities in patients with and without hypertension. Given the increasing rates of hypertension and its complex interplay with various health conditions, understanding these relationships is crucial for effective healthcare strategies. Methods: This retrospective observational study was conducted among 210 patients visiting an outpatient department of medicine, Holy Family Red Crescent Medical College & Hospital, Dhaka, Bangladesh. Participants were selected consecutively from those visiting for symptoms related to high blood pressure. Data on age, gender, body mass index (BMI), lifestyle factors, and comorbidities such as diabetes, obesity, and chronic kidney disease were extracted from medical records. Descriptive statistics and analytical methods were employed using SPSS software. Result: The study found a hypertension prevalence of 32.38% among the participants. Key sociodemographic findings included a higher representation of females and a majority age group of 50-59 years. Overweight and obesity were prominent among participants. A significant association between hypertension and diabetes mellitus was observed, with 83.82% of hypertensive participants having diabetes, compared to 42.96% in the non-hypertensive group. Other comorbidities like ischemic heart disease also showed significant associations with hypertension. However, some comorbidities like chronic kidney disease and stroke did not show a significant association. Conclusion: The study reveals a high prevalence of hypertension in the outpatient setting in Bangladesh, emphasizing the strong association with diabetes mellitus. It underscores the need for integrated healthcare approaches focusing on sociodemographic and metabolic risk factors. The findings call for targeted interventions and comprehensive healthcare strategies to manage hypertension and its related comorbidities in this population. This study contributes to the understanding of hypertension's prevalence and its interrelation with various health factors in Bangladesh.